INTRATUMORAL AMPLIFICATION HETEROGENEITY IN HER2/neu-POSITIVE BREAST CANCER MOLECULAR-GENETIC SUBTYPES - L. N. Vashchenko; L. E. Zavalishina; I. A. Pavlenko; P. E. Povilaitite (Сибирский научный медицинский журнал, 2019)
The defining feature of HER2/neu-positive Luminal B and HER2/neu-positive (non-luminal) subtype breast cancer is HER2/neu gene amplification and protein overexpression on cancer cell membrane. The HER2-targeted therapy is nowadays available for patients with HER2-positive breast cancer However, a significant fraction of HER2+ tumors acquire or possess intrinsic mechanisms of resistance, based on multiple factors, and genetic heterogeneity among them. The aim of our study was to quantify the heterogeneity of HER2/neu amplification in HER2/neu-positive Luminal B and HER2/neu-positive (non-luminal) subtypes of breast cancer. Material and methods. A retrospective analysis of 210 cases referred for dual probe fluorescence in situ hybridization (FISH) confirmation of an immunohistochemical equivocal 2+ result was performed. Results. Our results demonstrated a heterogeneous amplification pattern of HER2/neu gene, whose expression is a substantial cause of HER2/neu-positive Luminal B and HER2/neu-positive (non-luminal) subtypes of breast cancer, in 31 % of invasive breast cancer cases. As heterogeneous, we interpreted tumors containing cells with HER2/CEP17 ratio < 2 and gene copies 4 ≤ HER2/neu < 6, that is, those without HER2/neu amplification. The amount of heterogeneous tumors between HER2/neu-positive Luminal B and HER2/neu-positive (non-luminal) subtypes was not statistically significant. ROC analyses identified optimal cutoff point for HER2/CEP17 ratio as 2.6 for distinguishing heterogeneous tumors. Conclusion. The heterogeneity of HER2/neu amplification is determined by FISH in 31 % of cases and is independent of molecular breast cancer subtype. If a HER2/neu-positive breast cancer has HER2/CEP17 ratio ≤ 2,6, it contains minor subclones without HER2/neu amplification with a probability of 95 %. Our results demonstrated that HER2/neu amplification heterogeneity may be important for prognosis of survival and treatment decisions.